2003
DOI: 10.1542/peds.112.4.838
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes in Anemic Premature Infants: Are We Allowing the Hematocrits to Fall Too Low?

Abstract: Apparently "stable" anemic premature infants may be in a clinically unrecognized high cardiac output state, and some echocardiographic measurements do not improve within 48 hours after transfusion. The benefits of transfusion practices guided by measures of cardiac function should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 30 publications
0
42
0
3
Order By: Relevance
“…We have also demonstrated for the first time that the SVC blood flow volume decreases following blood transfusion during the first week of life and in the infants who were more than 4 weeks of age. A previous study has shown that anaemic preterm infants develop a high cardiac output state and this decrease significantly on blood transfusion 24 . There was no change in the SVC flow in the Group 2 infants perhaps indicating a more stable cardiovascular state or blood being transfused at a higher baseline Hb level before any haemodynamic decompensation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have also demonstrated for the first time that the SVC blood flow volume decreases following blood transfusion during the first week of life and in the infants who were more than 4 weeks of age. A previous study has shown that anaemic preterm infants develop a high cardiac output state and this decrease significantly on blood transfusion 24 . There was no change in the SVC flow in the Group 2 infants perhaps indicating a more stable cardiovascular state or blood being transfused at a higher baseline Hb level before any haemodynamic decompensation.…”
Section: Discussionmentioning
confidence: 92%
“…Other measures such as continuous measurement of cardiac output in paediatrics and neonates using transthoracic electrical bioimpedence is still in its early stage of validation and development 23 . It has been reported earlier that anaemic stable preterm infants could be at a clinically unrecognised high cardiac output state, which could lead to reduced oxygen delivery to brain 24 . This might in turn lead to cerebral haemorrhage and brain injury 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Nelle et al [28] ( n = 33) also noticed a significant drop in heart rate (from 161 to 149 beats per min; p = 0.005) following RCBT [28]. Contrastingly Dani et al [29] ( n = 14) and Alkalay et al [30] ( n = 32) found no difference in heart rate following RBCT. However, it was subsequently demonstrated that heart rate correlates positively with the measured blood volume of preterm infants born at 24–32 weeks of gestation [31].…”
Section: Physiological Adaptive Response To Anaemia and Blood Transfumentioning
confidence: 95%
“…[9][10][11][12] Anemia prematuritas terjadi pada bayi berat badan lahir rendah 1 sampai 3 bulan setelah lahir dengan kadar hemoglobin di bawah 7 mg/dL. Derajat anemia dan kadar hemoglobin tergantung dari derajat prematuritas.…”
Section: Penggunaan Eritropoetin Pada Anemia Prematuritasunclassified